1989
DOI: 10.1007/bf00316435
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase inhibition as a sequel of hydrogen sulfide intoxication: increases in brain catecholamine and 5-hydroxytryptamine levels

Abstract: Administration of sodium hydrosulfide (NaHS), an alkali salt of hydrogen sulfide (H2S) at doses of 10 and 30 mg/kg, corresponding to sublethal and lethal doses (0.66 and 2.0 X LD50) resulted in significant increases in regional catecholamine levels of the rat brain only after the dose of 2.0 x LD50 of NaHS. Whereas the cortex and the cerebellum showed little or no change in catecholamine content, the hippocampus, striatum and brainstem all showed increases in noradrenaline and adrenaline. Additional analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…H 2 S increases the levels of neurotransmitters c-amino butyric acid (GABA), glutamate, serotonin, dopamine, epinephrine, and norepinephrine (33). The levels of serotonin and catecholamine are increased by inhibition of monoamine oxidase (MAO) (74). H 2 S also enhances the effect of acetylcholine by suppressing the activity of its degradation enzyme, acetylcholinesterase.…”
Section: Synaptic Modulationmentioning
confidence: 99%
“…H 2 S increases the levels of neurotransmitters c-amino butyric acid (GABA), glutamate, serotonin, dopamine, epinephrine, and norepinephrine (33). The levels of serotonin and catecholamine are increased by inhibition of monoamine oxidase (MAO) (74). H 2 S also enhances the effect of acetylcholine by suppressing the activity of its degradation enzyme, acetylcholinesterase.…”
Section: Synaptic Modulationmentioning
confidence: 99%
“…This theory would support the concept that H 2 S is a broad-spectrum toxicant (Roth, 1993). In support of the diverse biological actions of sulfide, other reports have documented sulfide-mediated inhibition of monoamine oxidase (Warenycia et al, 1989), cholinesterase, and Na + /K + -ATPase (Reiffenstein et al, 1992) in rat brain. The lack of an effective antidote to H 2 S poisoning also appears consistent with multiple mechanisms of action (Reiffenstein et al, 1992).…”
mentioning
confidence: 74%
“…Since NaHS was considered a toxic substance, we injected NaHS (14 μmol/kg body weight/day) alone to control rats (n = 7) as the treatment control. Warenycia et al [30] reported an LD50 value of 15 mg/ kg body weight (approximately 192 μmol/kg body weight) for NaHS in rats, which is higher than the dosage we used. Another control group (n = 7) was supplied with sulphurous mineral water to exclude any toxic effect of H 2 S-rich water consumption.…”
Section: Experimental Designmentioning
confidence: 87%
“…Many studies have indicated that exogenous administration of the H 2 S donor NaHS to rats with myocardial injury reduces the mortality rate and the accumulation of plasmatic lipid peroxidation markers such as malondialdehyde (MDA) and conjugated dienes. At the same time, H 2 S may inhibit the formation of protein carbonyls induced in vitro by hypochlorous acid [30,71].…”
Section: Figmentioning
confidence: 99%